Inguinal Lipoblastoma Masquerading as Obstructed Omentocele in a Girl - Avilash Sahu; Manita Tamang; Bikasha Bihary Tripathy; Subrat Kumar Sahoo; Deepti Naik; Aditya Arvind Manekar; Manoj Kumar Mohanty (Journal of Indian Association of Pediatric Surgeons, 2024)
Lipoblastoma in the inguinal regional is a rare occurrence in children and can present as a surgical surprise during pediatric herniotomies. Irreducible inguinal hernia is one of the most common surgical problems dealt by pediatric surgery residents in emergency. We report a case of inguinal lipoblastoma presenting as irreducible groin swelling. Complete excision of the mass was done with no recurrence till date.